Comparison the Effect of Ferutinin and 17β-Estradiol on Bone Mineralization of Developing Zebrafish (Danio rerio) Larvae - Zare Mirakabad, Hoda (Int J Mol Sci, 2019)
There is an urgent need to develop novel drugs for osteoporosis which occurs due to estrogen deficiency. Phytoestrogens derived from medicinal plants would be the best alternative to chemical drugs with harmful side effects. The main purpose of the present study was to investigate the effect of ferutinin compared to 17β-estradiol (E2) on bone mineralization of zebrafish larvae. Regarding the lack of publications, the histology analysis was performed after exposure to E2 to find effective treatment on bone mineralization of developing zebrafish larvae. Then, the larvae were exposed to four concentrations of ferutinin at three time points to assess the mortality, the expression of some related genes and histology of the ceratohyal and hyomandibular of treated larvae. The RT-PCR result of the treatment groups demonstrated the similar expression pattern in the larvae which were exposed to 1.25 μg/mL of ferutinin and 2 µM of E2 at 2 dpf, which confirmed the result of histology analysis. In addition, RT-qPCR of high concentration of ferutinin and E2 demonstrated that bmp2a/b and esr1 were downregulated and upregulated when the larvae were exposed to 5 μg/mL of ferutinin and 10 µM of E2, respectively.